Metamorphic evolution of garnet-spinel peridotites from the Variscan Schwarzwald (Germany) - Kalt, Angelika; Altherr, Rainer (Geologische Rundschau, 1996)
Garnet-spinel peridotites form small, isolated, variably retrogressed bodies within the low-pressure high-temperature gneisses and migmatites of the Variscan basement of the Schwarzwald, southwest Germany. Detailed mineralogical and textural studies as well as geothermobarometric calculations on samples from three occurrences are presented. Two of the garnet-spinel peridotites have equilibrated at 680-770°C, 1.4-1.8 GPa within the garnet-spinel peridotite stability field, one of the samples having experienced an earlier stage within the spinel peridotite stability field (790°C, <1.8 GPa). The third sample, with only garnet and spinel preserved, probably equilibrated within the garnet peridotite stability field at higher pressures. These findings are in line with the distinction of two groups of ultramafic garnet-bearing high-pressure rocks with different equilibration conditions within the Schwarzwald (670-740°C, 1.4-1.8 GPa and 740-850°C, 3.2-4.3 GPa) which has previously been established (Kalt et al. 1995). The equilibration conditions of 670-770°C and 1.4-1.8 GPa for garnet-spinel peridotites from the Central Schwarzwald Gneiss Complex (CSGC) are similar to those for eclogites of the Schwarzwald and also correspond quite well to those for garnet-spinel peridotites from the Moldanubian zone of the Vosges mountains and of ecologites from the Moldanubian s.str. of the Bohemian Massif.